Efficient femtosecond optical parametric amplification and wavelength conversion in silicon waveguides - Liu, H.; Wang, Z.; Wen, J.; Huang, N.; Sun, Q. (ALT Proceedings, 2026)
Efficient  femtosecond  optical  parametric amplification and  wavelength conversion via four-wave  mixing  (FWM)  in  silicon  waveguides  are demonstrated.  In  the femtosecond  FWM  process, the spectra are greatly broadened, and it is difficult to achieve  efficient  wavelength  conversion  and parametric amplification when the pump and signal pulse widths are close to or less than 100 fs because of the spectral overlap. The spectral overlap can be suppressed  by  tailoring  the  dispersion  profiles of the  silicon  waveguides,  and  separable  spectra  are obtained  for  parametric amplification  with  200  fs pulses. On-chip parametric gain as high as 26.8 dB and idler  conversion  gain  of  25.6  dB  is  achieved with a low pump peak power over a flat bandwidth of 400 nm in a 10-mm-long dispersion engineered silicon waveguide. In addition, the impact of initial chirp  on  the  wavelength  conversion  is also investigated,  and  relative  narrower  FWM  spectra with most of the energy remain in the central peak can be obtained using appropriate initial chirp. The conversion  bandwidth  greater  than  500  nm  with peak  conversion  efficiency of  -1.6  dB  can  be obtained.